Replication-incompetent herpesvirus vector delivery of an interferon alpha gene inhibits human immunodeficiency virus replication in human monocytes. - Weir, J P (1993)
Human monocytes and macrophages are nondividing cells that serve as a major reservoir for human immunodeficiency virus (HIV) at all stages of infection. To investigate viral-mediated gene delivery as a means of inhibiting HIV replication in human monocytes, a replication-incompetent herpes simplex virus vector was developed that expressed human interferon alpha. Monocytes infected with this herpes simplex virus vector and then challenged with HIV showed dramatically reduced cytopathic effects and HIV replication compared to control treated monocytes. Similar effects on HIV replication were observed if monocytes were first infected with HIV and then treated with the recombinant vectors. These results demonstrate that replication-incompetent herpes simplex virus gene delivery of interferon alpha directly to human monocytes can greatly decrease HIV replication and suggest that such a vector might deliver therapeutically important genes directly to sites of HIV infection.